2013
DOI: 10.5489/cuaj.1402
|View full text |Cite
|
Sign up to set email alerts
|

Emergency versus elective ureteroscopic treatment of ureteral stones

Abstract: Introduction: This retrospective study investigates the role of the emergency ureteroscopic (URS) approach in the definitive treatment of ureteric stones. Methods: We reviewed all patients admitted for ureteric stones from May 2003 to December 2010. Those who underwent URS stone treatment were selected and stratified into emergency (EMG) and elective groups (ELG). Emergency URS is defined as URS being performed within 24 hours of admission to the emergency room. The main indication for emergency treatment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
7
7
0
Order By: Relevance
“…Availability of staff with a sub-speciality interest in stone surgery may also have influenced our high stone free rates. Our stone free rate also compared favourably to other emergency ureteroscopic management studies (89–98%) [7-10].…”
Section: Discussionsupporting
confidence: 63%
“…Availability of staff with a sub-speciality interest in stone surgery may also have influenced our high stone free rates. Our stone free rate also compared favourably to other emergency ureteroscopic management studies (89–98%) [7-10].…”
Section: Discussionsupporting
confidence: 63%
“…This was also reported in all previously published comparative studies [9,11,13,15,16]. The reported SFR of emergency URS ranged between 81% and 93% [8,9,[11][12][13][15][16][17][18]. We achieved a better SFR (96%) due to the use of laser lithotripsy in all cases.…”
Section: Discussionsupporting
confidence: 85%
“…The definition of emergency varied among the studies from 12 to 48 h from admission to the emergency room. Stone-free status was defined on postoperative imaging (KUB in 3 studies and CT scan in one), which was done at 1 month in most studies (Table 1) [16][17][18][19]. In six studies (4 prospective randomized controlled and 2 retrospective case-control studies), emergent ESWL (n = 356) was compared to delayed ESWL (n = 355).…”
Section: Resultsmentioning
confidence: 99%
“…An overall 5% complication rate was reported by a recent large audit form New Zealand [31]. In the four comparative studies, we identified and included only two major complications, which were reported by Matani et al, who had one ureteral perforation and one avulsion caused by stone basket [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation